Dr. Marc J. Salzman — Deep Plane Facelift — Sarasota - Salzman, Marc J. (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Marc J. Salzman, practicing in Sarasota, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003276; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; sarasota